Storm surge, seawater flooding, and sea-level rise paradoxically drive fresh surface water expansion - Julia A Cantelon; Barret L Kurylyk (Environmental Research Letters)
Coastal storms and sea-level rise (SLR) are expected to increase seawater flooding in low-elevation coastal zones. High sea levels and seawater flooding can drive groundwater table rise via ocean-aquifer connections. These dynamics are often overlooked but can cause groundwater flooding and salinization hazards, increasing freshwater security challenges for coastal communities and driving ecosystem transgressions. Field data and numerical modeling were used to evaluate how heavy rainfall, storm surge, and seawater flooding and infiltration during Hurricane Fiona (September 2022) and projected SLR impact groundwater levels, inland surface waters, and saltwater intrusion on Sable Island National Park Reserve, Canada. During the passage of Hurricane Fiona, precipitation increased groundwater and pond levels before seawater flooded the beach. Seawater flooding and infiltration caused a sharp rise in beach groundwater levels, which in turn caused inland pond levels to rise without coincident direct inputs from precipitation or seawater. Model simulations reveal that seawater infiltration on beaches flooded the subsurface and drove the observed inland groundwater rise and freshwater pond expansion. Simulations of projected SLR show that seawater flooding will only inundate a small area of land along the coast; however, inland groundwater rise and flooding, which is less well-studied, may inundate up to 30 times more land area. Further, groundwater flooding driven by rising sea levels decreases hydraulic gradients and increases saltwater intrusion via freshwater lens (FWL) contraction. Findings demonstrate that seawater flooding from coastal storms and SLR paradoxically cause concurrent fresh surface water expansion but FWL contraction. This study provides new insights into the spatiotemporal dynamics of island freshwater resources and highlights that unseen and often overlooked groundwater-surface water exchanges are critical to consider when evaluating coastal flooding and groundwater salinization hazards and management strategies for low-elevation coastlines.